THE PARADIGM OF ISLAMIC BOARDING SCHOOL EDUCATION BASED ON ETHICS, LAW, AND PSYCHOLOGY: A CRITICAL ANALYSIS OF KH. HASYIM ASY'ARI’S THOUGHT - Sutan Botung Hasibuan; Nur Hakima Akhirani Nasution; Mira Yanti Lubis; Fithri Choirunnisa Siregar; Sri Wahyuni; Desi Asmaret (Academic Bright Collaboration, 2026)
This study aims to analyze the concept of pesantren education from ethical, legal, and psychological perspectives by placing the thinking of KH. Hasyim Asy'ari is the main basis of the analysis. This research uses a qualitative approach based on literature studies with hermeneutic-critical analysis. The results of the study show that in the thinking of KH. Hasyim Asy'ari, pesantren education is built on the integration of adab, fiqh, and kiai-santri relations as the foundation for the formation of student character. This study found that adab is placed as the main requirement in the process of seeking knowledge, so that students are required to prioritize respect for teachers, sincerity, discipline, and self-control before achieving intellectual competence. In the normative dimension, fiqh is not only understood as a formal rule of worship, but also as an instrument for fostering social behavior and ethics in the daily life of students. Meanwhile, the kiai-santri relationship functions as an affective pedagogical model that emphasizes example, emotional closeness, and habituation of values through direct interaction in pesantren life. These findings show that pesantren education from the perspective of KH. Hasyim Asy'ari is oriented towards the integration of intellectual, spiritual, and moral development. This article emphasizes that this paradigm has high relevance in responding to the crisis of dehumanization of modern education. The novelty of this research lies in the effort of an integrative conceptual reconstruction, which synthesizes the dimensions of ethics, law, and psychology in one coherent epistemic framework, different from previous studies that tended to be partial, both sociological, historical, and pedagogical. These findings show that the paradigm is relevant in responding to the crisis of dehumanization of modern education as well as contributing to the development of a more integrative epistemology of Islamic education.